Numerical investigation of a novel device for bubble generation to reduce ship drag - Zhang, J. (2020)
For a sailing ship, the frictional resistance exerted on the hull of ship is due to viscous effect of the fluid flow, which is proportional to the wetted area of the hull and moving speed of ship. This resistance can be reduced through air bubble lubrication to the hull. The traditional way of introducing air to the wetted hull consumes extra energy to retain stability of air layer or bubbles. It leads to lower reduction rate of the net frictional resistance. In the present paper, a novel air bubble lubrication technique proposed by Kumagai et al. (2014), the Winged Air Induction Pipe (WAIP) device with opening hole on the upper surface of the hydrofoil is numerically investigated. This device is able to naturally introduce air to be sandwiched between the wetted hull and water. Propulsion system efficiency can be therefore increased by employing the WAIP device to reduce frictional drag. In order to maximize the device performance and explore the underlying physics, parametric study is carried out numerically. Effects of submerged depth of the hydrofoil and properties of the opening holes on the upper surface of the hydrofoil are investigated. The results show that more holes are favourable to reduce frictional drag. 62.85% can be achieved by applying 4 number of holes.